Feminization of Maroon Clownfish (Amphiprion biaculeatus, Bloch 1790) with 17β-Estradiol Hormonal Induction - Helena Sahusilawane; Agus Oman Sudrajat; Muhmmad Agus Suprayudi; Dinar Tri Soelistyowati; Ligaya I. T. A. Tumbelaka; Irzal Effendi (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research The 17β-estradiol hormone induction reduces the percentage of R values in skin and fin color by as much as 50-60%. The 17β-estradiol hormone induction increases total length and body weight, estradiol content, GIS and HIS, and also glucose content. The 17β-estradiol hormone induction shows mature development of the gonadal profile from functional male to functional female. Abstract   As maroon clownfish (Amphiprion biaculeatus) is a protandrous hermaphroditic fish, feminization process with 17β-estradiol hormone can be applied to accelerate the female broodstock candidate supply for further spawning effort. This study aimed to evaluate the feminization of A. biaculeatus with 17β-estradiol hormonal induction. This study used a completely randomized design with several hormone dosage, namely P0 (without 17β-estradiol hormone induction), P1 (0.5 Î¼g 17β-estradiol/g body), P2 (1.0 Î¼g 17β-estradiol/g body), and P3 (1.5 Î¼g 17β-estradiol/g body). These treatments were applied with three replications. Five fish composed of α-fish, β-fish, and three Î³-fish were reared in each aquarium for 90 days with a flowing water system. The α- and β-fish were then removed, while the Î³-fish was injected with hormone. Otohime pellet feed was fed three times a day until apparent satiation. The results showed that the 17β-estradiol hormone could induce 100% of the feminization process of male A. biaculeatus. The dosage of P3 obtained the lowest value percentage of red, green, blue (RGB), but showing the highest total of length and body weight (6.67±0.42 cm and 6.40±0.78 g, respectively), estradiol content (149.73±4.24 Ïg/mL), GSI and HSI (0.38±0.07% and 3.59±0.49%), and glucose content (4.67±0.64 mg/dL), followed by more mature gonad profile than other treatments. This condition indicates that fish in P3 treatment has been reversed as functional female. The average survival rate for the treatment was as high as 60%. Therefore, the application of 17β-estradiol hormonal induction is effective for the feminization process in A. biaculeatus as a protandrous hermaphroditic fish.